Application Of Aequorea Victoria Green Fluorescent Protein (Gfp) For Expression In Mycobacterium bovis BCG - Najamudin, Khairul Ezani (2007)
A potential marker, green fluorescent protein (GFP) derived from the jellyfish Aequorea victoria offer many advantages as a viability reporter, as it requires no external source of substrate nor cofactors to fluoresce but is dependent on the host cell being alive. Its use has been reported in M. tuberculosis, but the incorporation of potentially pathogenic strains for high throughput screening would raise issues of safety. Therefore, a safe strain such as the vaccine strains M. bovis BCG if made to express an easily detectable viability * reporter marker would be useful tool as a screening assay. In this study, a synthetic version of the wild type GFP gene sequence incorporating mycobacterial codon bias, was used to explore its potential as a marker of viability in the mycobacterial vaccine strain, M. bovis BCG. The synthetic gene designated as EzyGFP was successfully constructed by using assembly polymerase chain reaction (PCR). In the second approach, a modified version of GFP, GFPuv, was also tested as an alternative candidate. To propagate these genes in Escherichia coli and then deliver these genes into M. bovis BCG, mycobacterial shuttle vectors were constructed. To create mycobacterial shuttle vectors, the mycobacterial origin of replication was excised from a source plasmid, pNMN012, and ligated into plasmids designated as pEzyGFP, pGFPuvK and pGFPuvK65 respectively which contain the GFP gene of interest.